1985
DOI: 10.1021/ar00111a003
|View full text |Cite
|
Sign up to set email alerts
|

Steric interplay between alkyl groups bonded to planar frameworks

Abstract: Nonbonded interactions play an important role in determinng the three-dimensional structure and reactivity of organic molecules. The interaction energy, positive or negative, is usually interpreted in terms of repulsion between electron clouds as a result of the Pauli principle (van der Waals repulsion), London dispersion forces, Coulombic interactions, and delocalization of electrons due to through-space or through-bond interactions between atomic orbitals.Particular interest exists in interactions between al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…With regard to conformational effects in the sidechains themselves, it may well be that proton loss from methyl changes the conformation from one that is gear-clashed methyl-methyl (16,17) to one that is gear-meshed (or gearlocked) methyl-methylene. The possibility that this effect is favourable, together with a consideration of polarizability effects and hybridization changes at nitrogen, will be addressed in a subsequent publication.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to conformational effects in the sidechains themselves, it may well be that proton loss from methyl changes the conformation from one that is gear-clashed methyl-methyl (16,17) to one that is gear-meshed (or gearlocked) methyl-methylene. The possibility that this effect is favourable, together with a consideration of polarizability effects and hybridization changes at nitrogen, will be addressed in a subsequent publication.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, this involves a so-called gear-mesh mechanism. [19] This mechanism has been properly analyzed for aminoboranes solely in the case of {η 5 -[1-(diisopropylamino)borole]}metal complexes. [20] In the case of compound 4, it is noteworthy that the barrier to rotation is rather high, when compared with the aforementioned complexes (for the borole-Cr(CO) 3 complex: ΔG # coal = 42 Ϯ2 kJ mol -1 [20] ) as shown by the evaluated [21] energy of activation for 4 (ΔG # coal = 52 Ϯ2 kJ mol -1 ).…”
Section: Exchange Reactions Of the Selenasilanes 1 And 2 With Boron Hmentioning
confidence: 99%
“…It is known that o-xylene prefers the gear-clashed conformation 24 rather than the other gear-clashed form 25, or the gear-meshed form 26 (16,17).…”
Section: Gear Effectsmentioning
confidence: 99%
“…Roussel and co-workers (17,18) have recently examined the interplay between alkyl groups attached to aromatic rings and have rationalized reactivity differences in a number of systems on the basis that adjacent methyl and similar alkyl groups prefer to avoid the interactions shown in 25 and 26. Moreover, Schug and Viers (19) have calculated the energies of the rotational conformers of 2,3-lutidine and found that the gear-clashed rotamer 27 is more stable than the two gear-meshed rotamers 28 and 29 by 0.36 and 0.59 kcal mol-', respectively; it is more stable than the gear-clashed rotamer 30, which has a frontal interaction of hydrogens, by 1 .…”
Section: Gear Effectsmentioning
confidence: 99%